Anthropogenic impacts to the sediment budget of São Francisco River navigation channel using SWAT - Creech, Calvin T.; Siqueira, Rafael Brito; Selegean, James P.; Miller, Carol (International Journal of Agricultural and Biological Engineering, 2015)
The São Francisco River Basin, located in eastern Brazil, has undergone a significant amount of anthropogenic changes in the last several decades, such as agricultural expansion, irrigation activities, mining, and the construction of large dams. Together, these changes have altered the historic sediment budget and have led to an aggradation of sediments in the navigation channel, impacting the ability to efficiently ship agricultural commodities to regional ports. In an effort to aid decision makers in future waterway navigation planning, an international partnership between the Brazilian government agency CODEVASF and the US Army Corps of Engineers (USACE) was created. Through this partnership a SWAT model of the 630 000 km2 São Francisco River basin was developed to better understand both the historic and current sediment budget within the navigation channel. The SWAT model of the São Francisco River Basin was calibrated for hydrology and sediment loads. Monthly discharges were calibrated at 17 Agência Nacional de Águas (ANA) gages, with Nash-Sutcliffe efficiency (NSE) values ranging from 0.42 to 0.75 for an eleven year simulation. Sediment loads were calibrated to an ANA sediment gage located in the Middle São Francisco River Navigation Channel, with a PBIAS (Percent Bias) of 11.6. Based on model results, the aggradation rate of sediment in the São Francisco River and major tributaries has increased by approximately 20 Mt since Pre-European settlement of the basin (from approximately 7 Mt/a to 27 Mt/a). This increase has contributed to an impaired navigation channel due to shoaling of sandy sediments in the navigation channel. Keywords: sediment budget, aggradation rate, São Francisco River, anthropogenic impact, SWAT DOI: 10.3965/j.ijabe.20150803.1372 Online first on [2015-04-03] Citation: Creech C T, Siqueira R B, Selegean J P, Miller C. Anthropogenic impacts to the sediment budget of São Francisco River navigation channel using SWAT. Int J Agric & Biol Eng, 2015; 8(3): 140－157.